(3TQM GdETGQGJs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO ef jSJMb GdMeO dPGJg aEf GdYbhd eJWGHbI hGdCdHGH eJhGabg Ydi Cf GdYde CaVd GdSYGOGJ s
(3BNQgG (B:s
(3hGfG GjVkG jG CNj ai GdOjf hUGMHi ai WdH Gdjbjf dcKQI eG ajg ef GdMbGFb GdObjbI hGdeHGMK GdYejbI s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B94s
Keywords: (3GdadSaI hGdefWbs